2010
DOI: 10.1016/j.molcel.2010.01.037
|View full text |Cite
|
Sign up to set email alerts
|

The Histone Chaperone Nap1 Promotes Nucleosome Assembly by Eliminating Nonnucleosomal Histone DNA Interactions

Abstract: Summary The organization of the eukaryotic genome into nucleosomes dramatically impacts the regulation of gene expression. The delicate balance between transcription and DNA compaction relies heavily on nucleosome dynamics. Surprisingly, little is known about the free energy required to assemble these large macromolecular complexes and maintain them under physiological conditions. Here we describe the thermodynamic parameters that drive nucleosome formation in vitro. To demonstrate the versatility of our appro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

28
300
3
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 217 publications
(332 citation statements)
references
References 49 publications
28
300
3
1
Order By: Relevance
“…Free H2A–H2B preferentially interacted with tetrasomes and only once these were exhausted from the reaction H2A–H2B bound non‐specifically to the free DNA. In accordance with our structure and previously published data (Andrews et al , 2010), yNap1 is suppressing non‐specific DNA binding of H2A–H2B and thereby facilitates specific deposition of H2A–H2B and nucleosome assembly.…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…Free H2A–H2B preferentially interacted with tetrasomes and only once these were exhausted from the reaction H2A–H2B bound non‐specifically to the free DNA. In accordance with our structure and previously published data (Andrews et al , 2010), yNap1 is suppressing non‐specific DNA binding of H2A–H2B and thereby facilitates specific deposition of H2A–H2B and nucleosome assembly.…”
Section: Resultssupporting
confidence: 93%
“…Nap1 deletion only modestly reduces the amounts of nuclear H2A–H2B indicating that there are redundant H2A–H2B transport mechanisms (Mosammaparast et al , 2001). Instead, as previous analysis in a nap1 Δ strain reported significant non‐nucleosomal histone–DNA interaction of H2A–H2B, we favor the model that yNap1 prevents such non‐nucleosomal binding and thereby contributes to H2A–H2B deposition and nucleosome assembly (Andrews et al , 2010). …”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…The nucleosome can disassemble through the reverse reaction that starts with an opening of the (H3$H4) 2 tetramer-H2A$H2B dimers interface, followed by the release of H2A$H2B dimers from the DNA (14,28). It was also shown that H2A$H2B complexes with the DNA are effectively suppressed in vivo, even though the affinity of highly positively charged dimer to the DNA is substantial (29). Some PANS are likely to occur only in specific types of chromatin, e.g., centromeric (30).…”
Section: Introductionmentioning
confidence: 99%
“…This results in mixed populations of histone octamer on both donor and acceptor DNAs. Histone chaperones such as nucleoplasmin (Earnshaw et al 1980) and Nap1 (Ishimi and Kikuchi 1991) have also been shown to act as transfer agents under physiologically relevant salt conditions, and Nap1 has been proposed as route to measure nucleosome affinities (Andrews et al 2010).…”
Section: Nucleosome Assembly or Reconstitutionmentioning
confidence: 99%